2014
DOI: 10.1097/psy.0000000000000025
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Acute Stress on Cardiac Endocannabinoids, Lipogenesis, and Inflammation in Rats

Abstract: Objective Trauma exposure can precipitate acute/post-traumatic stress responses (AS/PTSD) and disabling cardiovascular disorders (CVD). Identifying acute stress-related physiologic changes that may increase CVD risk could inform development of early CVD-prevention strategies. The endocannabinoid system (ECS) regulates hypothalamic-pituitary-adrenal (HPA) axis response and stress-related cardiovascular function. We examine stress-related endocannabinoid system (ECS) activity and its association with cardiovascu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 43 publications
2
14
0
1
Order By: Relevance
“…Studying individual differences that influence post-trauma adaptation may generate clues about how anxiety states are triggered. Consistent with published data,~25% of TMT-exposed rats in our study failed to develop long-term anxiety-like behavior in the EPM (Fendt et al, 2005;Holman et al, 2014). In addition, TMT-resistant rats did not exhibit elevated levels of 2-AG in the amygdala compared with TMT-sensitive animals.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Studying individual differences that influence post-trauma adaptation may generate clues about how anxiety states are triggered. Consistent with published data,~25% of TMT-exposed rats in our study failed to develop long-term anxiety-like behavior in the EPM (Fendt et al, 2005;Holman et al, 2014). In addition, TMT-resistant rats did not exhibit elevated levels of 2-AG in the amygdala compared with TMT-sensitive animals.…”
Section: Discussionsupporting
confidence: 81%
“…Consistent with published data (Fendt et al, 2005;Holman et al, 2014), we found that~25% of the rats exposed to TMT did not develop long-term anxiety-like behavior. This led us to hypothesize that TMT exposure might differentially regulate 2-AG levels in resistant vs sensitive rats.…”
Section: Exposure To Tmt Mobilizes 2-ag In the Amygdalasupporting
confidence: 81%
“…Cardiac levels of 2-AG, but not AEA, are increased in preconditioning (Wagner et al 2006). However, acute stress was recently shown to decrease cardiac endocannabinoid levels (Holman et al 2014), which might indicate that an upregulation of the endocannabinoid system in the heart is a chronic effect. Upregulation of cannabinoid receptors has been shown in cardiac pathologies, particularly CB 2 , which is upregulated in chronic heart failure (Weis et al 2010), in aortic stenosis (Duerr et al 2013) and in ischaemia/reperfusion (Duerr et al 2014).…”
Section: Cardioprotective Effects Of Endocannabinoidsmentioning
confidence: 99%
“…Animal research has repeatedly shown a decrease in AEA in almost all brain regions investigated in response to both acute and chronic stress, which seems to contribute to HPA axis activation, as well as an anxiety phenotype (Morena et al, 2015). Furthermore, a peripheral decline of the N-acylethanolamides PEA and OEA in the aftermath of predator stress was observed in animals, too (Holman et al, 2014). Correspondingly, knockout of endocannabinoid receptors was associated with impaired stress coping and enhanced anxiety and depressive-like symptoms, while stimulation of the ECS reduced anxiety and stress-related behavioral impairments in stress-exposed rats (reviewed in Hill and Patel (2013)).…”
Section: Introductionmentioning
confidence: 99%